Gender differences in comorbidity of conduct disorder among adolescents in Northern Finland - Ilomaki, Essi; Hakko, Helina; Ilomaki, Risto; Rasanen, Pirkko; Study-70 Workgrp; Marttunen, Mauri (International Journal of Circumpolar Health, 2016)
Objectives: Conduct disorder (CD) refers to a pattern of severe antisocial and aggressive behaviour manifested in childhood or adolescence, with heavy costs to society. Though CD is a common psychiatric diagnosis among adolescents of both genders, gender differences in comorbidity of CD have been little studied. In this study we examined gender differences among adolescents with CD in causes for hospitalization, comorbid psychiatric diagnoses and somatic conditions. Study design: The original study sample consisted of 508 inpatient adolescents in Northern Finland (age 12-17); 155 of them (65 girls, 92 boys) fulfilled the DSM-IV criteria for CD. Methods: Diagnosis of CD and psychiatric comorbidities were obtained from the K-SADS-PL and somatic conditions from the EuropAsi. Results: As compared to boys with CD, suicidality (including suicidal ideation and behaviour) was significantly more commonly the cause of hospitalization among girls with CD (43% vs. 24%, p = 0.013). Among somatic conditions, there was a significant predominance in self-reported allergies among girls (60% vs. 25%, p Conclusions: Girls with CD seem to have an increased tendency to develop both comorbid psychiatric and somatic conditions as well as suicidality. New clinical aspects in treatment of CD and comorbid disorders among girls are discussed. Peer reviewed